Treatment failure and associated factors among first line patients on highly active antiretroviral therapy in Ethiopia: a systematic review and meta-analysis - Moges Agazhe Assemie; Muluneh Alene; Daniel Bekele Ketema; Selishi Mulatu (BMC, 2019)
Abstract Background Antiretroviral therapy (ART) restores immune function and reduces human immunodeficiency virus (HIV) related adverse outcomes. The results of previous studies in Ethiopia were replete with inconsistent findings; nonexistence of national representative figures and determinant factors are found as significant gap. The aim of this systematic review and meta-analysis was to assess the existing evidence on ART treatment failure and associated factors in Ethiopia. Methods Relevant studies on ART treatment failure were retrieved from international databases: PubMed, Google Scholar, Scopus, and Science Direct systematically prior to March 14, 2019. All identified studies reporting the proportion of first line treatment failure among HIV patients in Ethiopia were included. Two authors independently extracted all necessary data using a standardized data extraction format. A random-effects model was used to calculate pooled estimates and associated factors in Stata/se Version-14. The Cochrane Q test statistics and I 2 tests were used to assess the heterogeneity of the studies. Results From 18 articles reviewed; the pooled proportion of first line treatment failure among ART users in Ethiopia was 15.3% (95% CI: 12, 18.6) with (I 2 = 97.9%, p < 0.001). The subgroup analysis by World Health Organization (WHO) treatment failure assessment criteria were carried out, accordingly the highest prevalence (11.5%) was noted on immunological and the lowest (5.8%) was observed virological treatment failure. We had found poor adherence (OR = 8.6, 95% CI: 5.6, 13.4), not disclosed (OR = 2.1, 95% CI: 1.5, 3.0), advanced WHO clinical stage III/IV (OR = 2.4, 95% CI: 1.5, 3.8), change in regimen (OR = 2.5, 95% CI: 1.6, 3.9) and being co-infected (OR = 2.56, 95% CI: 2.2, 3.0) were statistically significant factors for treatment failure. Conclusion In this study, treatment failure among ART users in Ethiopia was significant. Adherence, co-infection, advanced WHO clinical stage, regimen change, and disclosure are determinant factors for treatment failure. Therefore, improve drug adherence, prevent co-infection, close follow up, and prevent HIV-drug resistance are required in future remedial efforts.